4D volcanic geology of Hachijo-jima islet, Izu-Bonin arc. Issue 15 (22nd August 2022) - Osozawa, Soichi; Ito, Hisatoshi; Nakazato, Hiroomi; Wakabayashi, John
ABSTRACT: This study combines detailed geologic mapping, tephrochronology, U-Pb zircon dating, and published drill core data to evaluate the time transgressive 3-dimensional (thus 4-dimensional) structure and evolution of the two volcanoes on Hachijo-jima of the juvenile Izu-Bonin intra oceanic arc. The regional Ata-Torihama tephra (Ata-Th; 0.24 Ma) and Kikai-Tozurahara tephra (K-Tz; 0.095 Ma) from Kyushu are intercalated within the voluminous proximal volcanic products. The silicic tuff cover of some supra-subduction zone ophiolites, that formed in a nascent arc setting, may be ancient analogs of the regional tephra derived from the adjacent but mature volcanic arc. The volcanic succession comprises submarine volcanic basement, marine volcaniclastic rocks, and terrestrial tuff intercalated with tholeiitic basalt and the exotic calc-alkaline tephra layers. The undissected Hachijo-Fuji stratovolcano (tholeiitic basalt) overlies marine volcaniclastics abutting the northwestern paleo sea cliffs of the older dissected volcano, Mihara-yama. Newly-described folding and normal faulting of the marine and overlying terrestrial volcaniclastic rocks record NW-SE shortening that may be associated with the collision of the Izu-Bonin arc with the Honshu arc, analogous to the NNE-SSW shortening observed for the Troodos ophiolite. The proto Hachijo-jima volcano emerged above the sea >0.24 Ma, and this date can be applied as a molecular biological calibration date for organisms on this island.